Immunoreactivity of Polish Lyme Disease Patient Sera to Specific Borrelia Antigens—Part 1 - Iwona Wojciechowska-Koszko (MDPI AG, 2021)
The diverse clinical picture and the non-specificity of symptoms in Lyme disease (LD) require the implementation of effective diagnostics, which should take into account the heterogeneity of Borrelia antigens. According to available guidelines, laboratories should use a two-tier serological diagnosis based on the enzyme-linked immunosorbent (ELISA) screening test and confirmation of the immunoblot (IB). The aim of the study was to investigate the immunoreactivity of LD patient sera to Borrelia antigens and to attempt to identify the genospecies responsible for LD using an ELISA–IB assay combination. Eighty patients with suspected LD and 22 healthy people participated in the study. All samples were tested with ELISA and IB assays in both IgM and IgG antibodies. In the case of the ELISA assay, more positive results were obtained in the IgM class than in the IgG class. In the case of the IB assay, positive results dominated in the IgG class. Positive results obtained in the IB assay most often showed IgM antibodies against the OspC and flagellin antigens, whereas the IgG antibodies were against VlsE, BmpA, OspC, p41, and p83 antigens. The IB assay is an important part of LD serodiagnosis and should be mandatory in diagnostic laboratories.